Design and physico-chemical characterization of nanowires and multicomponent metal oxide films with tailored mesostructure and crystallinity - Ostermann, Rainer; Justus Liebig University Giessen (My University, 2010)
Nanostructured metal oxides and metals are already of significant importance for diverse appli-cations, e.g. in catalysis or as electrode materials. Yet in many cases more progress could be achieved by combining the materials properties with a more suitable morphology than the commonly used thin films or nanopowders. During my PhD I used electrospinning as a versatile approach to generate nanofibers of metals and metal oxides with the ultimate goal of creating multi-component materials, such as oxide electrodes with nanofibrous conduction paths.As main challenges, several useful oxides (e.g. RuO2, transparent conducting oxides) and MOFs (metal organic frameworks) had not been available as nanofibers and if any, there were only a few complicated methods to control the fiber s morphology.In addition to preparing novel compact fibers, I studied the mechanisms of fiber formation and could thus develop new and straight-forward approaches to synthesize porous and hollow nano-fibers with increased surface areas. Moreover, I demonstrated the first examples of using fiber mats of metal oxides and metals to prepare model catalysts and highly efficient porous electrodes for sensors or fuel cells. I further integrated these electrodes into multi-component coatings for application in solar cells or in transparent conducting polymer films.
Synthese und physikalisch-chemische Charakterisierung von Nanofasern und Mehrkomponenten-Metalloxidfilmen mit kontrollierter Mesostruktur und Kristallinität
Keywords: Elektrospinnen; Nanofasern; Nanodrähte; Komplexe Elektroden; electrospinning nanofibers; nanowires; complex electrodes; ddc:540